Efficacy of early cognitive-linguistic treatment for aphasia due to stroke: A randomised controlled trial (Rotterdam Aphasia Therapy Study-3). (June 2017) - Nouwens, Femke; de Lau, Lonneke ML; Visch-Brink, Evy G; van de Sandt-Koenderman, WME (Mieke); Lingsma, Hester F; Goosen, Sylvia; Blom, Dineke MJ; Koudstaal, Peter J; Dippel, Diederik WJ
Introduction: One third of patients with acute stroke have aphasia. The majority receive speech and language therapy. There is evidence for a beneficial effect of speech and language therapy on restoring communication, but it is unknown whether and how efficacy of speech and language therapy is influenced by timing of treatment. We studied whether speech and language therapy early after stroke by way of intensive cognitive-linguistic treatment is more effective than no speech and language therapy in the Rotterdam Aphasia Therapy Study-3, a multicentre randomised single-blind trial. Methods and patients: Stroke patients with first-ever aphasia were randomised within 2 weeks of onset to either 4 weeks of early intensive cognitive-linguistic treatment (1 h/day) or no language treatment. Hereafter, both groups received regular speech and language therapy. Primary outcome was the score on the Amsterdam-Nijmegen Everyday Language Test, measuring everyday verbal communication, 4 weeks after randomisation. Secondary outcomes were Amsterdam-Nijmegen Everyday Language Test at 3 and 6 months. The study was powered to detect a clinically relevant difference of four points on the Amsterdam-Nijmegen Everyday Language Test. Results: Of the 152 included patients, 80 patients were allocated to intervention. Median treatment intensity in the intervention-group was 24.5 h. The adjusted difference between groups in mean Amsterdam-Nijmegen Everyday Language Test-scores 4 weeks after randomisation was 0.39, 95% confidence interval: [−2.70 to 3.47], p  = 0.805. No statistically significant differences were found at 3 and 6 months after randomisation either. Conclusion: Four weeks of intensive cognitive-linguistic treatment initiated within 2 weeks of stroke is not more effective than no language treatment for the recovery of post-stroke aphasia. Our results exclude a clinically relevant effect of very early cognitive-linguistic treatment on everyday language.